The power of advertising in shaping test drive intentions for Chinese electric vehicles: the moderating role of advertising literacy - Gong, Shuhui; De Costa, Mohd Feroz Shah; Mohd Hassan, Nurul'ain; Yang, Yuting; Liu, Lu (Malque Publishing, 2024)
China, as one of the world’s leading markets, has witnessed substantial growth in electric vehicle (EV) adoption, fueled by environmental benefits and strong government incentives. However, despite this growth, the transition from traditional internal combustion engine vehicles to EVs has been relatively slow, particularly among domestically produced Chinese brands. This study aims to analyze this marketing issue by investigating the impact of advertising on Chinese consumers’ intentions to test drive indigenous EVs—a crucial yet often overlooked step in the consumer decision-making process. The research focuses on three key advertising elements: creativity, informativeness, and emotional appeal, and examines their influence on consumer attitudes toward test driving EVs. By employing the Theory of Reasoned Action (TRA) as the theoretical framework, the study explores how these advertising components directly shape consumer attitudes and drive their intention to test drive EVs. Furthermore, the study delves into the moderating role of advertising literacy, utilizing Inoculation Theory to understand how consumers’ ability to critically evaluate advertisements influences their attitudes. The findings reveal that advertising plays a significant role in shaping consumer attitudes and behaviors. Importantly, the study also confirms that advertising literacy acts as a moderator in these effects, with more advertisingliterate consumers better equipped to critically assess and respond to the persuasive elements within advertisements. The study suggests that EV companies can more effectively encourage test drives and accelerate the adoption of electric vehicles in China by enhancing the creativity and emotional appeal of their advertisements while also taking into account the growing advertising literacy among consumers. By doing so, these companies can improve consumer engagement, leading to higher test drive rates and ultimately driving greater sales of domestically produced EVs.